The Strong Convex Functions and Related Inequalities - Xue Wang; Absar ul Haq; Muhammad Shoaib Saleem; Sami Ullah Zakir (Journal of Function Spaces)
The study of convex functions is one of the most researched of the classical fields. Analysis of the geometric characteristics of these functions is a core area of research in this field; however, a paradigm shift in this research is the application of convexity in optimization theory. The Jensen-Mercer type inequalities are studied extensively in recent years. In the present paper, we extend Jensen-Mercer type inequalities for strong convex function. Some improved inequalities in Hölder sense are also derived. The previously established results are generalized and strengthened by our results.